Microneedling: A means of collagen induction therapy - Pragya A Nair; Jinal Tandel (Wolters Kluwer Medknow Publications, 2021)
Background: Collagen induction therapy is a form of microneedling. It is cheap and effective and has less side effects than other alternative therapies. Purpose: It is done using dermaroller for the treatment of scars, wrinkles, stretch marks, hair growth, and transdermal delivery of substances like lipopeptides and antiaging products. Methods: It acts by stimulating collagen production, produces microwounds and thus release of various inflammatory mediators. It also increases electric potential, thus inducing cellular activity with release of cytokines and growth factors leading to wound healing with collagen induction. Results: There are various new modified instruments, and combination with other modalities of treatment increases its utility in different dermatological and cosmetic conditions. Conclusions: Microneedling is a simple, inexpensive procedure with no down time and good results in acne scars, hair loss and wrinkles.